PENGARUH PENDIDIKAN POLITIK TERHADAP PARTISIPASI POLITIK PEMILIH PEMULA PADA PEMILU 2019 DI SMA KECAMATAN BANTUL - Sari, Novia Santiya (Spektrum Analisis Kebijakan Pendidikan, 2019)
AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh pendidikan politik terhadap partisipasi politik pemilih pemula pada Pemilu 2019 di SMA Kecamatan Bantul. Penelitian ini adalah penelitian kuantitatif menggunakan metode survei. Tempat penelitian meliputi: SMA Negeri 1 Bantul, SMA Negeri 2 Bantul, SMA Negeri 3 Bantul, SMA Patria Bantul, SMA 17 Bantul, dan SMA Muhammadiyah Bantul. Populasi penelitian ini adalah seluruh siswa kelas XII di SMA Kecamatan Bantul dengan jumlah 903 siswa. Teknik pengambilan sampel dilakukan dengan teknik Simple Random Sampling berjumlah 211 siswa yang ditentukan dengan berdasarkan tabel Issac dan Michael dengan taraf kesalahan 10% . Instrumen penelitian berupa angket yang diuji validitas dan reliabilitas. Teknik analisis data dilakukan dengan uji normalitas dan uji linearitas. Hasil penelitian menunjukkan bahwa terdapat pengaruh yang signifikan antara pendidikan politik dengan partisipasi politik pemilih pemula di SMA Kecamatan Bantul sebesar 60,3%.Kata Kunci: Partisipasi Politik, Pendidikan Politik, Pemilu 2019AbstractResearch the effect of political education on the political participation of beginner voters in the 2019 election in Bantul district Senior High School aims to determine the effect of political education on the political participation of beginner voters in the 2019 election in Bantul district Senior High School. This research is quantitative research using survey method. The place of research was conducted in Bantul Senior High School which included: 1 Bantul Senior High School, 2 Bantul Senior High School, 3 Bantul Senior High School, Patria Bantul Senior High School, 17 Bantul Senior High School, and Muhammadiyah Bantul Senior High School. The population of this study was all students of class 12th who were beginner voters in Bantul district senior high school with a total of 903 students. The sample of this study was the beginner voters who came from the 12th grade in the Bantul district senior high school amount 211 students which is determined based on the Issac and Michael tables with an error rate of 10%. The research instrument was in the form of a poll on the influence of political education on the political participation of beginner voters in the 2019 election in Bantul district senior high school which has been tested for validity and reliability. The data analysis technique is done by normality test and linearity test. The results showed that there was a significant influence between political education and the political participation of beginner voters in the Bantul district senior high school. The magnitude of the influence of political education on the political participation of beginner voters in the 2019 election in Bantul High School is strong was in the amount of 60.3%.Keywords: Political Participation, Political Education, 2019 Election